The long and sinuous road to phage-based therapy of Clostridioides difficile infections - Umansky, Andrew A.; Fortier, Louis Charles (Frontiers in Medicine, 2023)
With the an:bio:c crisis and the rise in an:microbial resistance worldwide, new therapeu:c alterna:ves are urgently needed. Phage therapy represents one of the most promising alterna:ves but for some pathogens like Clostridioides difficile, important challenges are being faced. The perspec:ve of phage therapy to treat C. difficile infec:ons is complicated by the fact that no strictly ly:c phages have been iden:fied so far and current temperate phages generally have a narrow host range. C. difficile also harbors mul:ple an:phage mechanisms and the bacterial genome is o\en host of one or mul:ple prophages that can interfere with ly:c phage infec:on. Nevertheless, thanks to recent advances on phage host receptor recogni:on and improvements in gene:c tools to manipulate phage genomes, it is now conceivable to gene:cally engineer C. difficile phages to make them suitable for phage therapy. Other phage-based alterna:ves such as phage endolysins and phage tail-like bacteriocins (Avidocins) are also being inves:gated but these approaches also have their own limita:ons and challenges. Finally, but not the least, C. difficile produces spores that are resistant to phage aaacks and all current an:bio:cs, and this complicates therapeu:c interven:ons. This minireview gives a brief historical overview of phage work that has been done in C. difficile, presents recent advances in the field and addresses the most important challenges that are being faced, with poten:al solu:ons.